EMERGENCE OF STRATEGIC LEADERSHIP IN THE HEALTHCARE SECTOR: A BIBLIOMETRIC ANALYSIS - Bahadur, Ms. Shefali; Kushwaha, Dr. Rohit (The journal of contemporary issues in business and government, 2022)
The healthcare sector is a complex workplace where human resource management is of vital importance. The strategic leadership play an important role to direct the diversified workforce towards achieving the goals of organisation to ensure sustainability and competitiveness. The current study has highlighted the emergence of strategic leadership in the healthcare sector. A bibliometric analysis approach has been applied after extracting the date from the Scopus database in the domain of strategic leadership in healthcare sector. The data after the filtration has been analysed using VOS viewer and R-studio (Biblioshine). The findings will help in understanding of the contributions made since 1991 and will be useful to researchers working in this domain. An upsurge trend has been viewed in the publication of documents in this domain since the year 2015. With the application of word dynamics and thematic analysis the study presented the emerging themes in the domain.